(untitled) (Research, Society and Development, 2023)
Toxoplasmosis is the most frequent cause of brain damage with mass effect on the central nervous system (CNS) in immunocompromised patients. The clinical picture is characterized by symptoms compatible with encephalitis, which is the result of a process of reactivation of the chronic infection by the protozoan Toxoplasma gondii. This study in question is a simple literature review, carried out between March and April 2023, based on a database search: US National Library of Medicine (PubMed), Scientific Electronic Library Online (Scielo) and Google Scholar. The keywords used for the search were: "Neurotoxoplasmosis HIV" and "Cerebral toxoplasmosis HIV". Thus, the articles were filtered according to the main information about the pathology described, with the purpose of supplying information related to the theme and which were discussed in the following sessions: a) Epidemiology; b) Clinical manifestations; c) Diagnosis; d) Treatment. It is concluded that over time, there was a significant reduction in the incidence of cases of neurotoxoplasmosis in our country. The disease remains a relevant cause of morbidity and mortality in people with human immunodeficiency, making it necessary to recognize, diagnose and treat this pathogenesis effectively, since the period between diagnosis and initiation of treatment is decisive in morbidity and mortality.